The Art of Darkness Deception and Urban Operations - Gerwehr, Scott (RAND Corporation, 2000)
This research was undertaken to gain a better understanding of the relationship between deception and the urban environment, first to explore the power of deception when employed against U.S. forces in urban operations, and second to evaluate the potential value of deception when used by U.S. forces in urban operations.